2010
DOI: 10.1177/0748233710375947
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine as a photoprotective agent for diminishing phototoxicity

Abstract: Skin whitening with Chinese herbal medicine has been used in ancient Asia. However, phototoxicity of the active ingredient limits the application. The modified comet assay was used in the current study to detect DNA crosslinking induced by phototoxicity. Result showed that caffeine at 5 µmol/L was able to reduce 5-methoxypsoralen-induced phototoxicity with ultraviolet C (UVC) exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Caffeine has been reported to scavenge highly reactive free radicals and to defend crucial biological molecules against these species (Devasagayam et al, 1996). Furthermore, the work of Szeto and Tong (2010) showed that caffeine at 5.0 μmol/L reduced 5-methoxypsoralen-induced phototoxicity with UVC exposure. Caffeine has been used extensively as a cosmetic ingredient not only because of its bioactivity, but also due to its low toxicity profile (Nawrot et al, 2003; Doepker et al, 2016) and numerous works can be found in the literature reporting caffeine skin permeation (Zesch et al, 1979; Dias et al, 1999; Johnson et al, 2006; Herman and Herman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine has been reported to scavenge highly reactive free radicals and to defend crucial biological molecules against these species (Devasagayam et al, 1996). Furthermore, the work of Szeto and Tong (2010) showed that caffeine at 5.0 μmol/L reduced 5-methoxypsoralen-induced phototoxicity with UVC exposure. Caffeine has been used extensively as a cosmetic ingredient not only because of its bioactivity, but also due to its low toxicity profile (Nawrot et al, 2003; Doepker et al, 2016) and numerous works can be found in the literature reporting caffeine skin permeation (Zesch et al, 1979; Dias et al, 1999; Johnson et al, 2006; Herman and Herman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication showed that combining caffeine with such products reduces phototoxic reactions with UVC exposure—allowing such products to be used more safely. [ 30 ]…”
Section: Introductionmentioning
confidence: 99%